2004
DOI: 10.1128/mcb.24.8.3324-3336.2004
|View full text |Cite
|
Sign up to set email alerts
|

Human Spt6 Stimulates Transcription Elongation by RNA Polymerase II In Vitro

Abstract: Recent studies have suggested that Spt6 participates in the regulation of transcription by RNA polymerase II (RNAPII). However, its underlying mechanism remains largely unknown. One possibility, which is supported by genetic and biochemical studies of Saccharomyces cerevisiae, is that Spt6 affects chromatin structure. Alternatively, Spt6 directly controls transcription by binding to the transcription machinery. In this study, we establish that human Spt6 (hSpt6) is a classic transcription elongation factor tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
108
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(113 citation statements)
references
References 32 publications
5
108
0
Order By: Relevance
“…Interaction studies showed that DSIF genetically and physically associates with TFIIF, TFIIS, and CSB (Rad26) as well as the chromatin-related factors Spt6, FACT, Chd1, and the PAF complex Orphanides et al 1999;Costa and Arndt 2000;Jansen et al 2000;Krogan et al 2002b;Mueller and Jaehning 2002;Squazzo et al 2002;Lindstrom et al 2003;Simic et al 2003;Endoh et al 2004). In addition, Spt5 interacts with factors implicated in mRNA maturation and surveillance (see below) (Wen and Shatkin 1999;Andrulis et al 2002;Pei and Shuman 2002;Lindstrom et al 2003).…”
Section: Dsifmentioning
confidence: 99%
See 1 more Smart Citation
“…Interaction studies showed that DSIF genetically and physically associates with TFIIF, TFIIS, and CSB (Rad26) as well as the chromatin-related factors Spt6, FACT, Chd1, and the PAF complex Orphanides et al 1999;Costa and Arndt 2000;Jansen et al 2000;Krogan et al 2002b;Mueller and Jaehning 2002;Squazzo et al 2002;Lindstrom et al 2003;Simic et al 2003;Endoh et al 2004). In addition, Spt5 interacts with factors implicated in mRNA maturation and surveillance (see below) (Wen and Shatkin 1999;Andrulis et al 2002;Pei and Shuman 2002;Lindstrom et al 2003).…”
Section: Dsifmentioning
confidence: 99%
“…This finding supports the idea that Spt6 aids in maintaining chromatin structure during elongation. Studies using classical elongation assays on naked DNA in vitro demonstrated that Spt6 functions as an elongation factor that stimulates the transcription rate of RNAP II both autonomously and together with DSIF (Endoh et al 2004). Together, these results implicate Spt6 as a modulator of RNAP II activity during elongation, as well as a maintenance factor for chromatin structure.…”
Section: Spt6mentioning
confidence: 99%
“…1 Spt6 was later described as an essential nuclear protein. 2,3 Like Spt4 and Spt5, Spt6 is required for transcription elongation, 4,5,31,70 and co-localizes with Spt5 and RNA polymerase (Pol) II at transcriptionally active loci on Drosophila polytene chromosomes. 6,7 Spt6 interacts with the structured part of histone H3 and can deposit nucleosomes on DNA in a supercoiling assay.…”
Section: Introductionmentioning
confidence: 99%
“…Spt6 activates transcription elongation of many genes in vivo (11,(13)(14)(15), regulates histone H3 lysine 36 methylation, and participates in mRNA 3Ј-end processing and export (16 -18). Many research reports have indicated that Spt6 cooperates with another histone H2A⅐H2B chaperone named FACT (FAcilitates Chromatin Transcription) in the reassembly of chromatin in the wake of transcribing RNAPII (12, 19 -21).…”
mentioning
confidence: 99%